FAKTOR YANG MEMPENGARUHI KEJADIAN DISMENOREA PADA REMAJA PUTRI KELAS X DI MAN RANTAUPRAPAT TAHUN 2021 - Rika Handayani (Jurnal Gentle Birth, 2022)
Dysmenorrhea is pain in the stomach that comes from uterine cramps and occurs during menstruation. Dysmenorrhea usually results from the excessive release of certain prostaglandins, from uterine endometrial cells. Objectives: was to determine the age frequency distribution of menarche, duration of menstruation, menstrual cycle, body mass index, family history of dysmenorrhoea in grade X adolescent girls of MAN Rantauprapat in 2021.Method:This research type is an analytical survey with cross sectional design. The population in this study were 177 people with simple random sampling technique. Data analysis using Univariate, Bivariate and Multivariate analysis.Results: Bivariate analysis obtained from the Chi-Square test of menarche age showed that p-value .001<.05, menstrual cycle p-value .014 <.05, menstrual duration p-value .002 <.05, Body Mass Index p = value .002 <.05, family history p-value .004<.05. The binary logistic regression test results showed the most influencing variable was Family History with a value of .001 <.005 Exp (B) 4.852.Conclusion: there are effects of menarche age, duration of menstruation and family history of dysmenorrhea. The influencing factor is family history. It is hoped that the school will work together with the local health office to improve health, especially about reproductive health.